2018
DOI: 10.1111/liv.13712
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury, but not sepsis, is associated with higher procedure‐related bleeding in patients with decompensated cirrhosis

Abstract: Background Bleeding after low-risk invasive procedures can be life-threatening or can lead to further complications in decompensated cirrhosis patients. In unstratified cohorts of hospitalized patients with cirrhosis, the rate of procedure-related bleeding is low despite abnormal coagulation parameters. Our objective was to identify patients with decompensated cirrhosis at a high risk of developing procedure-related bleeding in whom the value of pre-procedure transfusions could be assessed. Methods Hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 21 publications
0
61
0
4
Order By: Relevance
“…To the Editor, I read with great interest, the manuscript by Hung et al, 1 Fourthly, the severity of liver disease, based on Model for endstage liver disease (MELD) score did not impact the occurrence of PPH in the current study. However in a study done by Pache et al, 4 the authors noted high MELD score and renal dysfunction as significant predictors to develop haemorrhagic complications after AP.…”
Section: Post-paracentesis Hemoperitoneum -Time To Become More Careful!mentioning
confidence: 59%
“…To the Editor, I read with great interest, the manuscript by Hung et al, 1 Fourthly, the severity of liver disease, based on Model for endstage liver disease (MELD) score did not impact the occurrence of PPH in the current study. However in a study done by Pache et al, 4 the authors noted high MELD score and renal dysfunction as significant predictors to develop haemorrhagic complications after AP.…”
Section: Post-paracentesis Hemoperitoneum -Time To Become More Careful!mentioning
confidence: 59%
“…2 As a fact, this study confirms the hypothesis that the acute perturbance of renal function-but not as a chronic condition since the prevalence of renal failure was similar in patients with bleeding events and controls-may induce a derangement in the coagulation balance of cirrhotic patients when this feeble balance is challenged by an invasive procedure such as paracentesis. 1,2 Moreover, despite the finding did not reach the threshold for statistical significance, likely due to the limited sample size, and was therefore not overemphasised by the authors, both AKI and sepsis were found in 38% of patients who developed post-paracentesis bleeding versus 10% of controls, and 61% of the cases of sepsis were associated with AKI, thus surmising that also the presence of infection may represent an additional risk factor for post-procedural bleeding in cirrhotic patients. 1 The important practice findings identified in the studies are supported by the evidence provided by other studies showing that renal impairment-likely through both an increased fibrinolytic activity and an alteration in platelet function-and infection-possibly due to the release of heparin-like factors-may increase the risk of bleeding within a milieu, such as ascites, that per se has fibrinolytic capacity.…”
Section: Bleeding After Paracentesis In Patients With Decompensated Cmentioning
confidence: 92%
“…We read with a great interest the recently published study by Hung and Garcia-Tsao that identified the presence of acute kidney injury (AKI) as the most important predictor of bleeding following paracentesis in patients with decompensated cirrhosis. 1 Indeed, although the yield of this study results may be limited by its setting (retrospective, chart review), we feel that the authors should be complimented for their effort in trying to provide a clinical evidence for a pathophysiological hypothesis that was mainly suggested by experts' panel opinions. 2 As a fact, this study confirms the hypothesis that the acute perturbance of renal function-but not as a chronic condition since the prevalence of renal failure was similar in patients with bleeding events and controls-may induce a derangement in the coagulation balance of cirrhotic patients when this feeble balance is challenged by an invasive procedure such as paracentesis.…”
Section: Bleeding After Paracentesis In Patients With Decompensated Cmentioning
confidence: 99%
“…This interaction will eventually upset the coagulation equilibrium and ultimately lead to bleeding or thrombosis. Recognition and treatment of external factors which precipitate acute hepatic decompensation may help mitigate risk . However, it is often challenging to estimate risk in patients with cirrhosis as currently available hemostatic measures do not accurately predict bleeding or thrombosis .…”
mentioning
confidence: 99%
“…Recognition and treatment of external factors which precipitate acute hepatic decompensation may help mitigate risk. 2,3 However, it is often challenging to estimate risk in patients with cirrhosis as currently available hemostatic measures do not accurately predict bleeding or thrombosis. 4 Accordingly application of alternative measures using more global assays of coagulation with viscoelastic testing (VET) of whole blood, such as thromboelastography (TEG) or rotational thromboelastometry (ROTEM), shows promise in hemostasis management.…”
mentioning
confidence: 99%